The Perceptions of Using Duolingo Application in Learning English for Student's Vocabulary Mastery - Fakhrurriana, Ria; Nisa, Aulia; Noni, Nurdin (BATARA DIDI : English Language Journal, 2024)
The objective of this study was to investigate the attitudes around the use of the Duolingo program as a tool for enhancing students' vocabulary proficiency in the English language. The present study used a quantitative research methodology. The researcher administered a questionnaire to a group of students on their use of the Duolingo program. The participants in this research consisted of students enrolled in the English department at IAIN Kediri. The study sample consisted of 30 students that were enrolled in the English department. The findings indicate that 70% of respondents selected the option "Agree" for item number 1. This suggests that the usage of the Duolingo program for English language learning positively impacts students' vocabulary proficiency. Furthermore, the overall results of the 10-item questionnaire indicate a general agreement among participants. The Duolingo program may be seen as a valuable tool for acquiring vocabulary. The Duolingo program is a valuable tool for acquiring proficiency in the English language, since it not only facilitates learning but also enhances student engagement by providing an enjoyable and non-monotonous learning experience. The empirical evidence suggests that Duolingo is a proficient instrument for acquiring language skills.  The use of the Duolingo program has shown to be a successful method for enhancing pupils' proficiency in vocabulary.